(untitled) (New York, 2004)
This edition marks the 25th year that Basic and Clinical Pharmacology by Katzung has been available for teaching students pharmacology. This remains the gold standard of useable texts for teaching pharmacology to medical students. In my opinion, this is the best editio
Keywords: Clinical pharmacology,Pharmacology